Aerogel and ionogel strain sensors - Tan, Melissa Siew Ting (2018)
The human skin displays many remarkable properties such high stretchability and intuitiveness, allowing us to perceive high degrees of sensitivity of contact pressure, texture and temperature. Scientists have been interested in mimicking these properties of skin using synthetic materials to create electronic-skin. One aspect of electronic-skin is the development of pressure or strain sensors using pressure- and strain-sensitive materials. These materials are capable of transducing mechanical deformation into changes in electrical signals, such as resistance, enabling use as sensors for prosthetics or wearables for health monitoring. Materials that display changes in resistance corresponding to mechanical deformation are piezoresistive in nature. Two such material systems, aerogels and ionogels, are investigated in this project. The microstructure, mechanical and electromechanical properties of these materials are analysed and their potential use as strain sensors in electronic-skin applications are evaluated. In the first part, a low density and electrically conductive aerogel polymer composite was fabricated using resorcinol formaldehyde and cross-linked carbon nanotubes. While the aerogel displayed high piezoresistive sensitivity, its low compressibility rendered it unsuitable for electronic-skin applications. In the second part, an ionically conductive composite (ionogel) formed between polyvinyl alcohol and an ionic liquid 1-Ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMI] [TFSI]) allowed higher compressibility, demonstrating high potential to be used in electronic-skin applications.